Study of the Verses of the Qur'an Interpreting Kepler's Laws in Physics - Iin Inayah (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
This study explores the relationship between the concept of Kepler's Law in physics with Islamic teachings and the Qur'an as the main reference source used as study material that conveys the views of the Islamic religion. This study uses a qualitative approach with a literature review method, this study analyzes several excerpts of verses in the letters in the Qur'an, including: Q.S. Fushshilat: 33, Q.S. Ar-Rahman: 5, Q.S. Yasin: 40 and Q.S. Al-Anbiya: 33. Physics literature as a supporter of in-depth theoretical studies. Allah states that the sun and moon, which are among the largest celestial bodies, move in their respective orbits very regularly. This movement causes changes in the seasons. By paying attention to these changes, humans can regulate various aspects of life, such as agriculture, trade, and education, and use these movements to calculate prayer times, calendars, eclipses, and so on. Kepler's Law explains the movement of planets in elliptical orbits around the sun, with Kepler's First Law stating that each planet moves in an elliptical path with the sun at one of its focuses. Kepler's second law states that an imaginary line connecting the sun and a planet sweeps out equal areas in equal times. The primary data source is the Qur'an, especially the verses, which are studied together with physics literature. The results of the study indicate that interpreting Kepler's laws in the context of the verses of the Qur'an provides a deeper understanding of the relationship between science and faith. The order of the universe described by Kepler's laws can be seen as a manifestation of the greatness and power of Allah.